2021
DOI: 10.1002/joc.6978
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of asymmetric change in diurnal temperature range in recent decades over different agro‐climatic zones of India

Abstract: Diurnal temperature range (DTR) is an important indicator of climatic change and a critical thermal metric to assess the impact on agriculture and human health. This study investigates the seasonal, annual and decadal changes in the spatio‐temporal trend in DTR and air temperatures (maximum: Tmax and minimum: Tmin) during 1951–2016 and solar radiation (Srad) during 1984–2016 over 14 different agro‐climatic zones (ACZs) in India. The changes in the DTR trend between two time periods:1951–2016 and 1991–2016 (rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 34 publications
(14 citation statements)
references
References 87 publications
0
14
0
Order By: Relevance
“…Figure 6 shows the variations of regionally averaged extreme SPEI and drought severity in urban and rural regions. It is intuitive that from 1981 to 2020, the drought aggravated under climate change and global warming (Lu et al., 2016; Mall et al., 2021; Zhai et al., 2010). At local scales, anthropogenic activities, especially urban expansion, substantially affected the drought events.…”
Section: Resultsmentioning
confidence: 99%
“…Figure 6 shows the variations of regionally averaged extreme SPEI and drought severity in urban and rural regions. It is intuitive that from 1981 to 2020, the drought aggravated under climate change and global warming (Lu et al., 2016; Mall et al., 2021; Zhai et al., 2010). At local scales, anthropogenic activities, especially urban expansion, substantially affected the drought events.…”
Section: Resultsmentioning
confidence: 99%
“…The results indicated that global warming could lead to weaker diurnal temperature variation due to night‐time warming in most regions, particularly over southern Taiwan in summer and autumn. The trend was consistent with other studies of DTR changes due to global warming (Mall et al ., 2021; Sun et al ., 2021). In addition, a slight DTR increase occurred over northwestern Taiwan in spring and winter because warming in the daytime was severe over these regions.…”
Section: Resultsmentioning
confidence: 99%
“…This asymmetric temperature change reduces normalDnormalTnormalR $\mathrm{D}\mathrm{T}\mathrm{R}$ (Dai et al., 1997; Easterling et al., 1997; Karl et al., 1993; Qu et al., 2014; Sun et al., 2019). Also, an increasing trend of normalDnormalTnormalR $\mathrm{D}\mathrm{T}\mathrm{R}$ is confirmed for some regions (Peralta‐Hernandez et al., 2009; Shahid et al., 2012), implying geographical and temporal variabilities (Dimri & Niyogi, 2012; Mall et al., 2021). For example, while the Indian arid deserts and warm‐temperate grasslands exhibit negative normalDnormalTnormalR $\mathrm{D}\mathrm{T}\mathrm{R}$ trends, its northeast coast and sub‐tropical forests show the opposite.…”
Section: Introductionmentioning
confidence: 93%
“…2 of 11 temporal variabilities (Dimri & Niyogi, 2012;Mall et al, 2021). For example, while the Indian arid deserts and warm-temperate grasslands exhibit negative 𝐴𝐴 DTR trends, its northeast coast and sub-tropical forests show the opposite.…”
Section: 1029/2022gl100029mentioning
confidence: 99%